2018
DOI: 10.1021/acsami.7b19658
|View full text |Cite
|
Sign up to set email alerts
|

Ceria Nanoparticles-Decorated Microcapsules as a Smart Drug Delivery/Protective System: Protection of Encapsulated P. pyralis Luciferase

Abstract: The design of novel, effective drug delivery systems is one of the most promising ways to improve the treatment of socially important diseases. This article reports on an innovative approach to the production of composite microcontainers (microcapsules) bearing advanced protective functions. Cerium oxide (CeO) nanoparticles were incorporated into layer-by-layer polyelectrolyte microcapsules as a protective shell for an encapsulated enzyme (luciferase of Photinus pyralis), preventing its oxidation by hydrogen p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 67 publications
1
21
0
Order By: Relevance
“…2B). The obtained cerium(IV) oxide nanoparticles possessed catalase-like properties, as we showed earlier by the polarographic method [25], which confirms their antioxidant activity.…”
Section: Resultssupporting
confidence: 85%
“…2B). The obtained cerium(IV) oxide nanoparticles possessed catalase-like properties, as we showed earlier by the polarographic method [25], which confirms their antioxidant activity.…”
Section: Resultssupporting
confidence: 85%
“…Recently, nanoceria (nano-CeO 2 ) has attracted remarkable attention owing to superb redox property and extensively utilization in biology including disease diagnosis, therapy, [9] and drug delivery. [10] Owing to reversible shift between Ce 3+ and Ce 4+ ions during the redox reaction, CeO 2 has the ability to simulate the behavior of superoxide dismutase (SOD) and catalase (CAT) via substantial surface oxygen vacancies, which can be applied to efficiently attenuate and eliminate ROS production. Recent years, increasing researches including us used nano-CeO 2 on inflammatory treatment and demonstrated that nano-CeO 2 could mitigate local inflammatory response by scavenging excessive ROS and playing an important role in suppressing M1 macrophage polarization through decreasing the expression of p65 to constrain the NF-κB signal pathway and decreasing the expression of TNF-a, IL-6, and IL-1β in macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…The high surface area of ultra-small cerium oxide nanoparticles determines their active interaction with various ions and biomolecules, which, ultimately, can lead to the loss of the enzyme-like properties of the nanoparticles. However, the integration of nanoceria into the polyelectrolyte microcapsule can protect the encapsulated substance from negative external factors, as we have shown earlier [41]. The integration of nanoceria into the middle layer of the microcapsule maintains the possibility of access of various forms of ROS and free radicals to the surface of nanoparticles, due to the porous structure of the polyelectrolyte matrix.…”
Section: Introductionmentioning
confidence: 84%